2020
DOI: 10.1111/vde.12840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diphenhydramine and cetirizine on immediate and late‐phase cutaneous allergic reactions in healthy dogs: a randomized, double‐blinded crossover study

Abstract: BackgroundCurrently, there is insufficient evidence to confirm oral diphenhydramine (DPH) efficacy to prevent mast cell degranulation and histamine release in dogs.Hypothesis/ObjectiveTo determine and compare the effects oral of DPH and cetirizine on the immediate‐ and late‐phase cutaneous allergic reactions in healthy dogs.AnimalsTwelve healthy laboratory beagle dogs.Methods and materialsThe study was designed as a randomized, double‐blinded crossover study in which each dog served as its own control; twice‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, studies indicated that cetirizine, a secondgeneration antihistamine, is more effective and safer than diphenhydramine because of its longer duration of action and less incidence of sedative side effects (3,4). Additionally, recent studies in both humans and experimental animals revealed that cetirizine was more potent than diphenhydramine in the treatment or prevention of allergic reactions (5,6). Cetirizine and diphenhydramine primarily exert anti-allergic properties by antagonizing histamine H1 receptors in peripheral tissues (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies indicated that cetirizine, a secondgeneration antihistamine, is more effective and safer than diphenhydramine because of its longer duration of action and less incidence of sedative side effects (3,4). Additionally, recent studies in both humans and experimental animals revealed that cetirizine was more potent than diphenhydramine in the treatment or prevention of allergic reactions (5,6). Cetirizine and diphenhydramine primarily exert anti-allergic properties by antagonizing histamine H1 receptors in peripheral tissues (1).…”
Section: Introductionmentioning
confidence: 99%